LINC01638 lncRNA activates MTDH-Twist1 signaling by preventing SPOP-mediated c-Myc degradation in triple-negative breast cancer. Issue 47 (22nd November 2018) - Luo, Liyun; Tang, Hailin; Ling, Li; Li, Nan; Jia, Xiaoting; Zhang, Zhijie; Wang, Xiaorong; Shi, Lejuan; Yin, Jiang; Qiu, Ni; Liu, Hao; Song, Ying; et al.
Abstract Breast cancer is a heterogeneous disease, and triple-negative breast cancer (TNBC) continues to be a serious health problem. The potential involvement of lncRNAs in TNBC progression remains unexplored. Here, we demonstrated that LINC01638 is highly expressed in TNBC tissues and cells. LINC01638 maintains the mesenchymal traits of TNBC cells, including an enriched epithelial-mesenchymal transition (EMT) signature and cancer stem cell-like state. LINC01638 knockdown suppresses tumor proliferation and metastasis both in vitro and in vivo. LINC01638 overexpression predicts a poor outcome of breast cancer patients. Mechanistically, LINC01638 interacts with c-Myc to prevent SPOP-mediated c-Myc ubiquitination and degradation. C-Myc transcriptionally enhances MTDH (metadherin) expression and subsequently activates Twist1 expression to induce EMT. Our findings describe LINC01638-mediated signal transduction and highlight the crucial role of LINC01638 in TNBC progression.